Evolution of Legal Consolidation of Language Policy of Russian Empire on Ukrainian Provinces in XIX – early XX Century - O. V. Shevchenko (Bulletin of Kharkiv National University of Internal Affairs)
The need to create an effective mechanism to ensure the implementation of language policy by our state has been increased at the present stage of the development of Ukraine and its legal system. It, on the one hand, will ensure the revival and spread of the Ukrainian language, and on the other will allow the development of national minority languages in accordance with the European Charter for Regional or Minority Languages (1992), the UN Declaration on the Rights of Persons Belonging to National or Ethnic, Religious and Linguistic Minorities (1992), the UN Resolution on the Rights of Persons Belonging to National or Ethnic, Religious and Linguistic Minorities (1995), The Oslo Recommendations on the Language Rights of National Minorities (1998) and other existing international legal acts. Historical experience can significantly help the successful implementation of measures aimed at improving the effectiveness of domestic legislation in this area. It will allow us not to repeat the mistakes of the past and take into account and use the positive developments. Unfortunately, domestic practice demonstrates a clear lack of attention to the study and use of such experience.